2020
DOI: 10.1002/aps3.11368
|View full text |Cite
|
Sign up to set email alerts
|

A new fine‐grained method for automated visual analysis of herbarium specimens: A case study for phenological data extraction

Abstract: Herbarium specimens represent an outstanding source of material with which to study plant phenological changes in response to climate change. The fine-scale phenological annotation of such specimens is nevertheless highly time consuming and requires substantial human investment and expertise, which are difficult to rapidly mobilize. METHODS:We trained and evaluated new deep learning models to automate the detection, segmentation, and classification of four reproductive structures of Streptanthus tortuosus (flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
1
33
0
1
Order By: Relevance
“…The combination of smaller flowers, more complex morphology, and background "noise" on Anemone specimens (e.g., overlapping structures) likely made both model training and phenophase detection more prone to error. This result supports the recent hypotheses that successful application of machine-learning to phenophase assessment will be dependent on species-specific morphological details (Goëau et al, 2020). Along these lines, plant morphological trait databases could help facilitate the identification of suitable taxa to be analyzed with machine-learning methods.…”
Section: Point Masking With Minor Modification Is Efficient and Produsupporting
confidence: 84%
See 3 more Smart Citations
“…The combination of smaller flowers, more complex morphology, and background "noise" on Anemone specimens (e.g., overlapping structures) likely made both model training and phenophase detection more prone to error. This result supports the recent hypotheses that successful application of machine-learning to phenophase assessment will be dependent on species-specific morphological details (Goëau et al, 2020). Along these lines, plant morphological trait databases could help facilitate the identification of suitable taxa to be analyzed with machine-learning methods.…”
Section: Point Masking With Minor Modification Is Efficient and Produsupporting
confidence: 84%
“…Although Goëau et al (2020) found that training data from point masks, like those generated from CrowdCurio, produced less accurate results than those derived from fully masked training data, obtaining the latter is time intensive and difficult to scale to large numbers of specimens. Whereas Goëau et al (2020) produced three type of training data, "point masks" (produced from a 3 × 3-pixel box around a manual point marker); (ii) "partial masks" (extensions of point masks to include partial segmentation using the Otsu segmentation method (Otsu, 1979); and (iii) manually produced "full masks" of each reproductive structure, we only used modified partial masks (derived from point markers) with Mask R-CNN. These modified partial masks were scaled to the size of reproductive structures for each species and yielded high accuracy and efficiency for phenophase detection and counting.…”
Section: Point Masking With Minor Modification Is Efficient and Produmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are very promising for extracting a broad range of accurate annotations in a fully automated way. Such approaches are also being applied to identification of plant phenophase (i.e., bud, flower, fruit), which is important for assessing the effects of climate change on plant growth and reproduction and for comparing plant responses with those of pollinators, migratory birds, and other species that rely on plants for food and/or nesting sites (see, e.g., Lorieul et al, 2019;Pearson et al, 2020;Brenskelle et al, 2020;Goëau et al, 2020). Likewise, other evolutionary or ecological traits, such as leaf shape and size, leaf margins, and flower color, could also potentially be scored from images of herbarium specimens.…”
Section: Plants Meet Machines: Prospects In Machine Learning For Planmentioning
confidence: 99%